2015
DOI: 10.1111/bju.12651
|View full text |Cite
|
Sign up to set email alerts
|

Review of appendiceal onlay flap in the management of complex ureteric strictures in six patients

Abstract: ObjectivesTo evaluate appendiceal onlay flap ureteroplasty for repairing complex right proximal and mid-ureteric strictures. Patients and MethodsBetween August 2006 and August 2012 four women and two men (mean age 34.2 years) underwent right laparoscopic appendiceal onlay flap ureteroplasty. The mean stricture length was 2.5 cm. Stricture formation was secondary to impacted ureteric stones in three patients and failed pyeloplasty for congenital pelvi-ureteric junction obstruction in the remaining three. Each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…In addition, Duty et al . showed that appendiceal onlay ureteroplasty is a feasible option for managing patients with complex proximal and mid‐ureteral strictures of the right side . The onlay flap involved anastomosing the detubularized appendix to the posterior wall of the longitudinally opened ureter, which preserved the benefits of appendiceal interposition, but decreased the potential disadvantages.…”
Section: Appendiceal Interpositionmentioning
confidence: 99%
“…In addition, Duty et al . showed that appendiceal onlay ureteroplasty is a feasible option for managing patients with complex proximal and mid‐ureteral strictures of the right side . The onlay flap involved anastomosing the detubularized appendix to the posterior wall of the longitudinally opened ureter, which preserved the benefits of appendiceal interposition, but decreased the potential disadvantages.…”
Section: Appendiceal Interpositionmentioning
confidence: 99%
“…While distal ureteric strictures can be managed with reimplantation techniques, the bladder may not be able to reach mid or proximal ureteral strictures, and alternative reconstruction techniques are necessary ( 13 ). One such technique is the appendiceal interposition.…”
Section: Appendix Onlaymentioning
confidence: 99%
“…The tip of the appendix was transected and discarded, the lumen was flushed, and the appendix was detubularized along the antimesenteric border. The appendiceal flap was sutured to the opened ureteric segment as an onlay ( 13 ). The procedure was performed on 6 patients.…”
Section: Appendix Onlaymentioning
confidence: 99%
“…In human medicine, proximal ureteral obstructions may result from urolithiasis and after endoscopic treatment for urolithiasis, radiation therapy, trauma, thermal energy associated with laparoscopic therapy, retroperitoneal fibrosis, and iatrogenic injury . In addition, proximal ureteral obstructions can occur in children associated with congenital ureteropelvic junction obstructions .…”
Section: Introductionmentioning
confidence: 99%
“…When techniques for reconstruction of the proximal ureter in humans are being considered, there are several guiding surgical principles including techniques that allow for a wide, tension free and water tight anastomoses; the preservation of blood supply; and complete excision of the underlying pathology to prevent stricture recurrence . Surgical techniques currently performed in man include ureteroureterostomy, transureteroureterostomy, downward nephropexy, ureterocalicostomy, Boari bladder flap, psoas hitch, bowel interposition, pyeloplasty, renal autotransplantation, and nephrectomy . The technique chosen often depends on the location of the obstruction as well as its length.…”
Section: Introductionmentioning
confidence: 99%